1993
DOI: 10.1007/bf00190140
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated innervation of sinus hair follicles in rats

Abstract: Unmyelinated nerve fibres comprise approximately one third of the innervation of rodent sinus hair follicles but their function is unknown. They may play a role as high-threshold sensory fibres, or may be autonomic efferents controlling the vascular sinus. In the present experiments capsaicin and surgical sympathectomy were used to establish whether these unmyelinated fibres are afferent fibres or autonomic efferents. The deep vibrissal nerves of mystacial follicles (C1 and C4) and a non-mystacial follicle (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
5
11
1
Order By: Relevance
“…However, others have reported no reduction in the unmyelinated fiber count in the deep vibrissal nerves following sympathectomy, suggesting that the fibers serve a sensory function (Waite and Li, 1993). This is in accordance with our present results, which demonstrate that the inner-sinus plexus fibers are DOR-immunoreactive, do not display TH or RT-97 immunoreactivity, but do colocalize with CGRP-ir.…”
Section: Discussionsupporting
confidence: 93%
“…However, others have reported no reduction in the unmyelinated fiber count in the deep vibrissal nerves following sympathectomy, suggesting that the fibers serve a sensory function (Waite and Li, 1993). This is in accordance with our present results, which demonstrate that the inner-sinus plexus fibers are DOR-immunoreactive, do not display TH or RT-97 immunoreactivity, but do colocalize with CGRP-ir.…”
Section: Discussionsupporting
confidence: 93%
“…The deep vibrissal nerves leave their parent nerve in the subcutaneous tissue, ascend through the intervibrissal space in the dermis, and penetrate the dense collagenous capsule at the level between the lower and middle thirds of the follicle [Maklad et al, 2004]. This basic innervation pattern of the deep vibrissal nerve is similar to that described in previous studies [Waite and Li, 1993;Rice et al, 1997;Ebara et al, 2002]. A recent study has demonstrated the dual innervation of the deep vibrissal nerve in the Florida manatee [Sarko et al, 2007]; however, the deep vibrissal nerve innervation pattern was singular in the present study, not dual ( fig.…”
Section: Innervation Of the Deep Vibrissal Nervesupporting
confidence: 84%
“…However, human microneurography experiments again showed in the late 1990s that C-LTMRs are relatively common in human skin (30,58). Anatomical studies had provided hints that some hair follicles may be innervated by unmyelinated afferent fibers (23,77), but until recently direct evidence had been lacking.…”
Section: Unmyelinated Hair Follicle Afferents: Tactile C-fibersmentioning
confidence: 99%